Influences on food choice - Barrett, Neil; O'Brien, Karyn; Shortal, Justin; Video Education Australasia (Bendigo, Vic.: Video Education Australasia, 1995)
Reviews the historical development of food pattern, looks briefly at the composition of diet today and the examines 13 influences on food choices.
Presenters, Karyn O'Brien, Justin Shortal.
Keywords: Food habits -- Australia; Nutrition -- Australia; Diet -- Australia